The Little Data Book on Gender 2013 (World Bank e-Library., 2013)
This handy pocket guide is a quick reference for users interested in gender statistics. It presents gender-disaggregated data for more than 200 countries in an easy country-by-country reference on demography, education, health, labor force, political participation and the Millennium Development Goals. The book?s summary pages cover regional and income group aggregates.